FRI0190 Clinical outcomes from a nationwide non-medical switch from originator to biosimilar etanercept in patients with inflammatory arthritis after 5 months follow-up. results from the danbio registry. (15th June 2017) - Glintborg, B; Sørensen, IJ; Loft, AG; Esbesen, J; Lindegaard, H; Jensen, DV; Danebod, K; Dieperink, S; Hendricks, O; Hansen, IMJ; Linauskas, A; Kristensen, S; et al.
Abstract : Background: In Denmark, biological drugs are provided free by the hospitals to the patients via a tax-based system. In 2015 a non-medical switch from originator infliximab to CT-P13 was conducted (1). According to national guidelines in April 2016, a non-medical switch from originator (ETA, Enbrel® 50 mg/week) to biosimilar etanercept (SB4, Benepali®) was dictated when SB4 was marketed, including patients with inflammatory rheumatic diseases treated in routine care. Objectives: To investigate 3 months' disease activity and 5 months' treatment withdrawal in ETA-treated patients (pts) with rheumatoid arthritis (RA), psoriatic arthritis (PsA) and axial spondyloarthrits (SpA), who were switched to SB4 and monitored prospectively in the DANBIO registry. Methods: Pts with RA/PsA/SpA followed in DANBIO since start of first bDMARD were included. Disease activity at 3 months before switch (pre-switch), at the switch and after 3 months (post-switch) and changes over time (Δpre-switch and Δpost-switch) were calculated. Disease flare was defined as ΔDAS28≥1.2 (RA/PsA) or ΔASDAS≥1.3 (SpA). Factors associated with withdrawal (gender/age/diagnosis/bDMARD-treatment-no/comedication methotrexate/baseline CRP/patient's global score) were explored by multivariable Cox regression analysis. Results: In total, 1548 switch pts were identified (891 RA, 335 PsA, 322 SpA). 60% were women, age (median (IQR) 56 (44–65) yrs)). Prior ETA treatment duration was 5.2 (3.2–8.0) yrs. ETA was the first biological treatment in 49%, and the second in 33% of pts. Concomitant MTX was given in 60% (RA)/49% (PsA)/15% (SpA). Median follow-up time was 154 (110–178) days. Disease activity remained largely unchanged 3 months prior to vs. after the switch (Table). The proportion of patients with disease flare pre-/post switch was 8%/13% (RA), 9%/13% (PsA), 5%/5% (SpA). Overall, 129 pts (9%) stopped SB4 treatment during 5 months' follow-up (Table). Prior ETA treatment duration in these patients was 4.5 (2.7–7.1) years. Higher patient's global score (HR 1.12/cm, 95% CI (1.05–1.21), p=0.002) and no concomitant methotrexate (HR 2.28 (1.48–3.52), p<0.001) at baseline were associated with withdrawal. Conclusions: In 1548 patients with inflammatory rheumatic diseases treated with ETA for >5 years, disease activity was largely unaffected in the majority of patients 3 months after non-medical switch to SB4 and comparable to the fluctuations observed in the 3 months prior to the switch. Several patients (≈9%) stopped treatment during 5 months follow-up. Higher patient's global score and no use of methotrexate were associated with withdrawal. Longer follow-up will offer additional understanding of the potential efficacy and safety consequences of the non-medical switch. References: Glintborg et al. Arthritis Rheumatol. 2016; 68 (suppl 10): Abstract no 951. Acknowledgements: Data analysis was partly financially supported by Biogen. Disclosure of Interest: B. Glintborg Grant/research support from: Abbvie, Biogen, I. Sørensen: None declared, A. G. Loft: None declared, J. Esbesen: None declared, H. Lindegaard: None declared, D. Jensen: None declared, K. Danebod: None declared, S. Dieperink: None declared, O. Hendricks: None declared, I. M. Hansen Grant/research support from: Roche, A. Linauskas: None declared, S. Kristensen: None declared, L. Andersen: None declared, M. Hossein: None declared, H. Nordin: None declared, B. Andersen: None declared, S. Chrysidis: None declared, J. Raun: None declared, N. Manilo: None declared, J. Grydehøj: None declared, E. Dalgaard: None declared, D. Pedersen: None declared, N. Krogh: None declared, M. Hetland Grant/research support from: Orion, BMS, AbbVie, Biogen, Pfizer, MSD, Eli Lilly